Insurance Development and Economic Growth : Evidence from India - Chopra, Monika; Saldi, Rupish (Indian Journal of Finance, 2019)
Insurance as a component of the financial structure can be a vital element in the growth of economic activities as well as can enable an increase in the economy's size, employment, managed assets, etc. In light of this expected role played by insurance, the current study looked at how the development of insurance in an economy fosters its growth as well as factors contributing to the evolution of India's insurance market. For this purpose, we studied insurance development indicators, that is, insurance density and penetration and investigated their link with GDP growth. Later, we checked the role of demographic factors such as age dependency ratio, urban population growth, life expectancy, and adult literate population in explaining insurance density and penetration. Using Toda Yomamoto VAR Granger causality framework, the study found two-way causality between insurance development and economic progress supporting a feedback hypothesis on two-way association between insurance development and economic growth. Further, using ARDL bounds approach, we found a long run causality between life expectancy and insurance development. The study concluded by pointing the role of risk aversion caused by life uncertainty in promoting insurance development. It also brought out the importance of insurance development in economic growth, with scope of further research on similar lines by considering the role of insurance and its broader investigations.